An optimal design tool for the design of continuous beam using MS-Excel - Chua, Jun Ping (2014)
As a continuation to the previous year project, the objective of this project is to develop an optimal design tool to assist structural engineers in the design of continuous beam subjected to bending only. Using this tool, engineers will be able to design steel beams in a progressive manner, conducting the necessary analysis and design checks, at the same time allowing the engineers to select the most economical steel section for construction. This will eliminates the need for manual design and calculation, and possibly reducing human errors and provide a significantly more precise and accurate design. The development of the design tool is in accordance to the Eurocode 3 standard using Microsoft Excel and Visual Basic for Application (VBA) as the main platforms. In this report, the development process of the design tool and the required analysis and design checks on the steel beams are discussed. The report will also run through the design tool from the start of the steel beam design process to the completion of the design with the aim of helping engineers have a better understanding of the design tool. Being possibly the first of its kind, this design tool will serve as a reference for future developers to develop a more comprehensive design tool to cater for more realistic applications and can also be used for educational purposes in various institutions.